System for digital professional development of university teachers - Nataliia Morze; Oksana Buinytska; Liliia Varchenko-Trotsenko; Svitlana Vasylenko; Dariya Nastas; Anastasiia Tiutiunnyk; Svitlana Lytvynova (Academy of Cognitive and Natural Sciences, 2022)
The article highlights the issues of developing a system for digital competence of the teacher. The paper describes the research that resulted in the development and implementation of the system for digital professional development for university teachers at the Borys Grinchenko Kyiv University. The principle of system adaptation is realized in two directions: to time possibilities of testing and minicourse passing; to needs of teachers according to professional direction and disciplines taught. A model of organisation of this system based on self-assessment, self-education and micro-teaching principles has been developed. The main structural elements of the system are diagnostic test and sets of minicourses. The approaches to the formation of the diagnostic test, including ensuring its integration, variability and validity, as well as the principle of its use in order to establish the level of digital competence of teachers in accordance with the developed corporate standard of digital competence were applied in detail. Using the example of the compulsory level of digital competence Analyst-Researcher (A) the use of mini-course sets for Integrator (B1), Expert (B2), Leader (C1) and Innovator (C2) levels are described. The system allows teachers to build their own professional development trajectory as a digital footprint reflected in a personal study, and the use of embedded business intelligence tools provides a visualised holistic picture of digital professional performance. The place of the system and its further development for professional development in the digital twin of the educational institution is highlighted.